Abscisic Acid Effects On Water And Photosynthetic Characteristics Of Two Ecotypes Of Atriplex Halimus L. - Bidai, Y.; Achour, A.; Belkhodja, M. (University of Eloued جامعة الوادي, 2016)
The aim of this study is to compare the water and photosynthetic characteristics of two xerophilic ecotypes of Atriplex halimus (L.). Seeds collected from two different sites Djelfa and Oran are germinated in controlled greenhouse. After 6 months, the plantlets were treated 21 days with increasing concentrations of abscisic acid (0M, 10-6 M and 10-3 M). The results show that ecotype of Djelfa reduced water loss through transpiration because of high stomatal resistance. Consequently the content of chlorophyll a and b decrease significantly compared to Oran ecotype which show an increase of the osmotic potential and relative water content. Osmotic adjustment to reduce dehydration and maintain a good photosynthesis seems efficient in Oran ecotype.
Articale in Journal of fundamental and Applied Sciences Vol. 08, N. 02
Keywords: Phytohormone; drought; xerophyte; water status; stomatal resistance; chlorophyll